Mandala Theory Of Arthaśāstra And Its Implementation Towards Indonesia's Geopolitics And Geostrategy - Ni Kadek Surpi; Ni Nyoman Ayu Nikki Avalokitesvari; I Made Gami Sandi Untara (Jurnal Penelitian Agama Hindu, 2020)
This article examines the Mandala Theory, which was formulated as a concept of national defense by Acarya Cakaya or Kautilya more than 2000 years ago. The Mandala theory has been used since ancient India. Various major kingdoms in Southeast Asia, including in the Nusantara, also use it even to be implemented in the defense system, embodied in their geopolitics and geostrategy. By some authors, Mandala Theory is still considered traditional and military heavy. But in fact, this theory is inseparable from other defense concepts such as diplomacy (The concept of Mantrashakti, Ṣāḍguṇya, and Cautr Upaya) which are the strength of a state. This qualitative study is using critical discourse analysis and Gadamer's hermeneutics. Mandala's theory as a defense concept in Chanakya's view was explored from several major theories in Arthaśāstra and its implementation in Indonesian geopolitics and geostrategy. However, the current defense needs to be adjusted, especially regarding the involvement of non-military elements, to build a strong state. Therefore, national defense theory should not only understood by state administrators. But also the intellectual cadre of state defense, and even all of its people.